APAKAH PROFITABILITAS TERDONGKRAK KARENA PROGRAM GREEN ACCOUNTING DAN KINERJA LINGKUNGANNYA? BUKTI DARI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wulan Sari; Zul Azmi; Linda Hetri Suriyanti (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
This study aims to examine the effect of green accounting implementation and environmental performance on the profitability of manufacturing companies. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2015-2020. The sample was taken using a purposive sampling method so that there were 12 companies that met the criteria which can be downloaded from the www.idx.co.id website. Multiple regression analysis technique was used to test the hypothesis. The results show that the application of green accounting programs and environmental performance have a significant influence on the profitability of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2020. The application of green accounting is a driving force for increasing the company's positive image. Environmental performance can also be an indicator that supports the company's success. Good company performance followed by good environmental performance will increase the ability to compete.